The role of political parties in multi-level environmental governance in the European Union and Germany - A. D. Lisenkova (Управление)
The subject of the study is the involvement of political parties in multi-level environmental governance in the European Union, using Germany and its federal states as an example. This article describes the theoretical and practical foundations of multi-level governance. The place of European parties and their national member parties from Germany in the institutional system and decision-making process of environmental policy has been defined. For practical illustration, the climate policy guidelines of Germany’s main national parties (the Christian Democratic Union of Germany and the Christian Social Union in Bavaria, the Social Democratic Party of Germany, the Alternative for Germany, the Free Democratic Party of Germany, the Left and the Alliance 90 / The Greens) and their European affiliations (the European People’s Party, the Party of the European Socialists, the Alliance of Liberals and Democrats for Europe, the European Green Party and the Party of European Left) were compared with an emphasis on the new targets for reducing greenhouse gas emissions. The unique opportunity for parties to participate in environmental policymaking at all key levels, which is not limited to parliamentary institutions has been highlighted. Appointments to environmental positions at different levels often correlate with membership of the most environmentally oriented parties, although the level of environmental involvement may differ between national parties and their European affiliations. Among other things, this has to do with participation in governing coalitions and dependence on a senior partner in them, as shown by the examples of the Bundestag and the Landtag of Baden-Württemberg. The final decision depends heavily on the unity of the coalition at federal and state level, whereas in the European Parliament there is a great differentiation of opinions, which allows even the most influential European People’s Party to be blocked from voting.